Grief, Mindfulness and Neural Predictors of Improvement in Family Dementia Caregivers - Jain, Felipe A.; Connolly, Colm G.; Moore, Leonardo C.; Leuchter, Andrew F.; Abrams, Michelle; Ben-Yelles, Ramzi W.; Chang, Sarah E.; Ramirez Gomez, Liliana A.; Huey, Nora; Lavretsky, Helen; Iacoboni, Marco (Frontiers in Human Neuroscience, 2019)
Background: Family dementia caregivers often suffer from an immense toll of grief while caring for their loved ones. We sought to identify the clinical relationship between grief, depression and mindfulness and identify neural predictors of symptomatology and improvement. Methods: 23 family dementia caregivers were assessed at baseline for grief, mindfulness and depression, of which 17 underwent functional magnetic resonance imaging (fMRI). During fMRI, caregivers were shown faces of either their dementia-stricken relative or that of a stranger, paired with grief-related or neutral words. In 9 subjects, post fMRI scans were also obtained after four weeks of either guided imagery or relaxation. Robust regression was used to predict changes in symptoms with longitudinal brain activation changes as the dependent variable. Results: Grief and depression symptoms were correlated (r = 0.50, p = .01), and both were negatively correlated with mindfulness (r = -.70, p = .0002; r = -.52, p = .01). Relative to viewing strangers, caregivers shown pictures of their loved ones (picture factor) exhibited increased activation in the dorsal anterior cingulate gyrus and precuneus. Improvement in grief but not mindfulness or depression was predicted by increased relative brain activation in the precuneus and anterior cingulate (different subregions from baseline). Viewing grief-related vs. neutral words elicited activity in the medial prefrontal cortex and precuneus. Conclusions: Caregiver grief, depression and mindfulness are interrelated but have at least partially nonoverlapping neural mechanisms. Picture and word stimuli related to grief evoked brain activity in regions previously identified with bereavement grief. These activation foci might be useful as biomarkers of treatment response.